Modern approaches to web resource creation using progressive design technology - Парненко, Валерія Сергіївна (Eastern-European Journal of Enterprise Technologies, 2012)
The features of Web resourse creation using progressive design technology are analyzed, the basic perspectives of development of this technology in web design are determined